Bacterial Infectious Scleritis: A Case Report - Liang Q; Wang Y; Ma X (Infection and Drug Resistance)
Qianqian Liang,1– 3 Yuerong Wang,1– 3 Xiubin Ma1– 3 1Eye Institute of Shandong First Medical University, Qingdao Eye Hospital of Shandong First Medical University, Qingdao, People’s Republic of China; 2State Key Laboratory Cultivation Base, Shandong Key Laboratory of Eye Diseases, Qingdao, People’s Republic of China; 3School of Ophthalmology, Shandong First Medical University, Qingdao, People’s Republic of ChinaCorrespondence: Xiubin Ma, Qingdao Eye Hospital of Shandong First Medical University, Qingdao, 266071, People’s Republic of China, Tel +86-0532-85876380, Email maxiubin2005@126.comPurpose: To report the outcomes of a case of bacterial infectious scleritis managed with thorough debridement and antibiotic irrigation therapy.Observations: A patient presented with severe infectious scleritis secondary to Pseudomonas aeruginosa subsequent to cataract surgery. The scleral abscess was cleaned completely and rinsed with ciprofloxacin every day in the treatment room. Over the next week, the conjunctival and scleral wounds healed. The patient’s condition was observed to be stable over the next 3 months, and the uncorrected vision acuity in the treated eye improved to 0.22 logMAR.Conclusions and Importance: This case highlights the utilization of thorough debridement and antibiotic irrigation to preserve the globe and good vision while treating severe infectious scleritis.Keywords: infectious scleritis, Pseudomonas aeruginosa, thorough debridement, antibiotic irrigation